Clinical features and choice of the revascularization method in patients with stable coronary heart disease and preserved left ventricular ejection fraction - Yu.A. Borkhalenko; О.J. Zharinov; K.O. Mikhaliev; О.А. Yepanchintseva; А.V. Khokhlov; B.М. Тоdurov (Кардіохірургія та інтервенційна кардіологія)
The aim – to establish the clinical features influencing the choice of revascularization method in patients with stable coronary artery disease and preserved left ventricular ejection fraction (LV) in real-life clinical practice. Materials and methods. The cross-sectional single-center retrospective study analyzed data from clinical and instrumental examination of 115 patients with coronary artery disease prepared for coronary artery bypass grafting (CABG) (n = 71) or coronary stenting (n = 44). Results. The two groups had no significant differences regarding demographic and anthropometric indices, most laboratory parameters and background medications. However, patients of the CABG group had more often hypertension, mostly 2 and 3 degrees (95.8 % vs. 84 %), stable angina III and IV functional class (51.3 % vs. 28.7 %). In addition, these patients had more severe diastolic dysfunction and higher left ventricular end-diastolic volume. According to the coronary angiography, CABG group patients more often had unprotected left main (UPLM) disease (28.2 % vs 4.6 %, p = 0.004), and three-vessel disease without UPLM (45 % vs 31.8 %, p < 0.001). Instead, one-vessel disease was more often registered in the stenting group. Significant differences in quality of life by majority measures of MLHFQ and SF-36 questionnaires in the compared groups were not found. Conclusions. Features of the patients with coronary artery disease and preserved left ventricular function, selected for CABG, are more pronounced stable angina (III and IV functional class) and heart failure, often the presence of UPLM and multivessel disease. Group of patients selected for coronary artery stenting was at least not inferior to CABG group regarding quality of life indicators. In patients with specific anatomical variants of coronary lesions potential impact upon quality of life is a key to choosing the method of revascularization.